The extended mind of public space: how urban design shapes human experience - Gruosso, Stefania; Del Signore, Marcella; Di Cinzio, Andrea (Frontiers in Built Environment, 2025)
The current debate on urban design emphasizes a multidisciplinary approach that integrates spatial, cognitive, and experiential perspectives. This paper introduces the concept of “The Extended Mind of Public Space,” following a theoretical framework that explores how public spaces serve as extensions of human cognition, perception, and emotion. By shaping thoughts, behaviors, and social interactions, public spaces—such as squares, parks, and gathering places—become real laboratories for human experience and wellbeing. This study identifies and examines six design paradigms—ritual-based, body-based, sensory-based, atmospheric-based, performance-based, and intelligent/augmented-based—each addressing a unique interaction between the body, mind, senses, and the built environment. Using qualitative analysis of case studies from the past 20 years, the research highlights the innovative strategies employed in contemporary public spaces to foster urbanity and enhance human experiences. Key findings reveal that these paradigms are not isolated but interdependent, offering a synergistic framework for creating inclusive, human-centered public spaces. Additionally, the study underscores the importance of interdisciplinary collaboration, incorporating insights from architecture, neuroscience, and environmental psychology to design spaces that promote wellbeing, encourage participation, and positively influence behavior. The paper concludes by advocating for a typological upgrade of the existing public space definitions, aligning them with the cognitive city paradigm. This research establishes a methodological foundation for future scientific studies that integrate environmental psychology and neuroscience into urban planning, redefining urban design theories through a human-centered approach.